2021
DOI: 10.3390/ani11020437
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Expression of Testicular TAS1R3 from Prepuberty to Sexual Maturity in Congjiang Xiang Pigs

Abstract: Testicular expression of taste receptor type 1 subunit 3 (T1R3), a sweet/umami taste receptor, has been implicated in spermatogenesis and steroidogenesis in mice. We explored the role of testicular T1R3 in porcine postnatal development using the Congjiang Xiang pig, a rare Chinese miniature pig breed. Based on testicular weights, morphology, and testosterone levels, four key developmental stages were identified in the pig at postnatal days 15–180 (prepuberty: 30 day; early puberty: 60 day; late puberty: 90 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…It is well known that cAMP and protein kinase A (PKA) are crucial synthesizing testicular steroids. For example, in our previous experiments, mice after saccharin sodium injection caused an elevation in taste signaling factors (T1r3, Gα) and also detected an elevation in cAMP concentration, which in turn increased the expression of steroidogenic enzymes (StAR, CYP11A1, 3β-HSD and CYP17A1 ( Gong et al, 2021 ). In addition, the taste receptor T1r1 is linked to cAMP ( Meyer et al, 2012 ).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is well known that cAMP and protein kinase A (PKA) are crucial synthesizing testicular steroids. For example, in our previous experiments, mice after saccharin sodium injection caused an elevation in taste signaling factors (T1r3, Gα) and also detected an elevation in cAMP concentration, which in turn increased the expression of steroidogenic enzymes (StAR, CYP11A1, 3β-HSD and CYP17A1 ( Gong et al, 2021 ). In addition, the taste receptor T1r1 is linked to cAMP ( Meyer et al, 2012 ).…”
Section: Introductionmentioning
confidence: 81%
“…T1R3 and its downstream protein Gα in late spermatogenic cells and Leydig cells have been observed in mice and pigs ( Spinaci et al, 2014 ; Gong et al, 2016b ; Gong et al, 2021 ). Besides, T2Rs has ectopic expression during spermatogenesis in human ( Governini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The expression data were normalized using the expression of the β-actin we used as the internal reference. The relative changes in gene expression were then calculated using the relative quantification method 2 − ΔΔCT [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our previous miRNA microarray data showed that miR-181c or miR-181d (miR-181c/d) is highly expressed in testes from sexually immature boars at 60 days old compared with sexually mature boars at 180 days old [10]. At sexually immature stage, Sertoli cells have proliferative capacity and the BTB is not yet fully formed; at the sexually mature stage, Sertoli cells no longer undergo cell proliferation and have formed a blood-testis barrier [11][12][13][14]. The miR-181c is found to disturb the blood-brain barrier and F-actin organization in brain blood vessel endothelial cells by downregulating its target gene 3-phosphoinositide-dependent protein kinase-1 [15].…”
Section: Introductionmentioning
confidence: 99%